The Patriarchal Power for Traditional Chinese Women in Pearl S. Buck’s “The Good Earth” - Mosleh Habibullah; Ulfa Sufiya Rahmah (OKARA: Jurnal Bahasa dan Sastra, 2023)
The subordination of women in society has become a common phenomenon. The woman's life in traditional Chinese culture is portrayed as someone who must be obedient, submissive, polite, have manners, and be loyal to her husband and others. The Good Earth novel reflects the life of traditional Chinese women in patriarchal power and the role of female characters. This study aims to describe the Chinese community traditions that govern women's lives in the late 19th and early 20th centuries and elucidate the orthodox tradition's effect on the role of female characters. The method applied was Library Research through the Sociological and Psychological Approaches. The data were obtained from The Good Earth novel and secondary data, such as the library, books, critics, writer’s biography, and a novel summary. The research revealed that women had a low position in social status in ancient China. We are familiar with the name of the patriarchy set by Confucius, as illustrated by figure O-lan, Wang Lung's wife as a female character in the novel and character theories, and his contribution will be used as the basis for analysis. The research summarizes that the teachings of the Confucian Philosophy of Culture influence patriarchal power.